How patients with multiple sclerosis acquire disability - Lublin, Fred D; Häring, Dieter A; Ganjgahi, Habib; Ocampo, Alex; Hatami, Farhad; Čuklina, Jelena; Aarden, Piet; Dahlke, Frank; Arnold, Douglas L; Wiendl, Heinz; Chitnis, Tanuja; Nichols, Thomas E; et al. (Brain (London, England : 1878), 2022)
Patients with multiple sclerosis acquire disability either through: (1) Relapse-associated worsening (RAW), or (2) progression independent of relapse activity (PIRA). This study addresses the relative contribution of relapses to disability worsening over the course of the disease, how early progression begins, and the extent to which multiple sclerosis therapies delay disability accumulation. Using the Novartis-Oxford MS (NO.MS) data pool spanning all multiple sclerosis phenotypes and pediatric multiple sclerosis, we evaluated ∼200,000 EDSS transitions from >27,000 patients with ≤15 years follow-up. We analyzed three datasets: (A) A full analysis dataset containing all observational and randomized controlled clinical trials in which disability and relapses were assessed (N = 27,328); (B) All phase 3 clinical trials (N = 8364); and (C) All placebo-controlled phase 3 clinical trials (N = 4970). We determined the relative importance of RAW and PIRA, investigated the role of relapses on all-cause disability worsening using Andersen-Gill models, and observed the impact of the mechanism of worsening and disease modifying therapies (DMTs) on the time to reach milestone disability levels using time continuous Markov models. PIRA started early in multiple sclerosis, occurred in all phenotypes, and became the principal driver of disability accumulation in the progressive phase of the disease. Relapses significantly increased the hazard of all-cause disability worsening events: Following a year in which relapses occurred (vs a year without relapses), the hazard increased by 31-48%; all p < 0.001. Pre-existing disability and older age were the principal risk factors for incomplete relapse recovery. For placebo-treated patients with minimal disability (EDSS 1) it took 8.95 years until increased limitation in walking ability (EDSS 4) and 18.48 years to require walking assistance (EDSS 6). Treating patients with DMTs delayed these times significantly by 3.51 years (95% confidence limit: 3.19, 3.96) and by 3.09 years (2.60, 3.72), respectively. In relapsing-remitting multiple sclerosis (RRMS), patients who worsened exclusively due to RAW events took a similar time to reach milestone EDSS values compared with those with PIRA events; the fastest transitions were observed in patients with PIRA and superimposed relapses. Our data confirm relapses contribute to the accumulation of disability, primarily early in multiple sclerosis. PIRA starts already in RRMS and becomes the dominant driver of disability accumulation as the disease evolves. Pre-existing disability and older age are the principal risk factors for further disability accumulation. Using DMTs delays disability accrual by years, with the potential to gain time being highest in the earliest stages of multiple sclerosis.